Scaling the capacities to adapt to a changing climate: Experiences of the AMIA Climate Resilient Villages, Philippines - Koerner, Jana; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Vidallo, Rene R.; Gonsalves, Julian Francis (2019)
Since 2015, the Philippines Department of Agriculture (DA) mainstreams climate resilient agriculture (CRA) across all its programs, functions, and agencies through the national and system-wide AMIA program. As part of this AMIA program, DA created “AMIA villages” in 21 regions, following the example of CCAFS Climate-Smart Villages. The learnings from this study suggest that the AMIA villages already possess the needed ingredients for developing into sustained innovation platforms. The functional capacities of the AMIA village leaders could still be strengthened with regard to addressing institutional bottlenecks at all levels, e.g. by developing further change management, negotiation and advocacy skills. This is not surprising given the early stage of implementation of many AMIA villages, and the iterative design of the process.